The Relationships among international trade, trade openness, financial development and economic growth: the case of Thailand - Jumpanoi, Pakarat; Wanasilp, Wanakiti (Business Administration and Economics Review, 2023)
This study is conducted to investigate the relationships among international trade, trade openness, financial development and economic growth in Thailand over the period 1997-2021 using time series analysis. The ADF test is used to verify the order of integration of the variables and the Johansen cointegration methodology is employed to investigate the long run relationship among these variables. It is found that there exists the long run relationship among these variables. The Error Correction Model (ECM) is also estimated to test the short run adjustment of the system. It is found that the system is able to adjust back to its long run equilibrium at the rate of 58 percent of the disequilibrium in each successive time period after the shock occurs. In addition, the direction of causality between these variables is estimated by Granger Causality Test. It is found that there is unidirectional causality from import to economic growth, economic growth to export, import to export, financial development to export and import to financial development; and bidirectional causality between trade openness and economic growth, financial development and economic growth, trade openness and export, and financial development and trade openness.